Income Equality in the Nordic Countries: Myths, Facts, and Lessons - Mogstad, Magne; Salvanes, Kjell G.; Torsvik, Gaute (Journal of Economic Literature, 2025)
Policymakers, public commentators, and researchers often cite the Nordic countries as examples of a socioeconomic model that combines low income inequality with prosperity and growth. This article critically assesses that claim by integrating theoretical perspectives and empirical evidence to explain how the Nordic model functions and why these countries experience low inequality. Our analysis suggests that income equality in the Nordics is largely driven by a significant compression of hourly wages, reducing returns to labor market skills and education. This appears to result from a wage bargaining system characterized by strong coordination within and across industries. This finding challenges other commonly cited explanations for Nordic income equality, such as redistribution through the tax transfer system, public spending on goods that complement employment, and public policies promoting equal skills and human capital. We consider broader lessons for economies aiming to reduce inequality and conclude by highlighting several under-explored or unresolved questions. (JEL D31, E23, H23, J24, J31, J52)